PENGARUH MODEL PEMBELAJARAN TIPE THINK TALK WRITE (TTW) TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS PESERTA DIDIK KELAS VIII SMP NEGERI 25 PADANG - Aulia, Mutiara Nurul (Departemen Matematika, 2023)
Mathematical communication ability is one of the most important abilities in learning mathematics. However, in reality the students' ability to communicate mathematically in class VIII SMP Negeri 25 Padang is relatively low. The solution sought is the Think Talk Write (TTW) learning model. This study aims to describe the growth of students' mathematical communication skills in class VIII SMP Negeri 25 Padang while the TTW model is being used and to assess whether students' mathematical communication skills taught by the TTW model are superior when compared to direct learning. Quasi-experimental research, nonequivalent posttest-only control group designs, and descriptive research are all examples of this sort of study. For the academic year 2022–2023, the population was decided to be the class VIII students of SMP Negeri 25 Padang. Quizzes and the overall evaluation of the statistical material's mathematical communication abilities served as the instruments. The results of the quiz data analysis resulted in the development of students' abilities in mathematical communication as long as the TTW model was used for each indicator. P-value = 0.000 is the outcome of hypothesis testing with a significance threshold of 0.05. means that so reject . So it was found that the ability of students to communicate mathematically using the TTW model was better when compared to direct learning.Keywords– Think Talk Write (TTW) Learning Models, Mathematical Communication Skills, Direct Learning Models